Application of Distribution Power Electronic Transformer for Medium Voltage - Prashant Kumar (Institute of Advanced Engineering and Science, 2014)
In this paper a distribution power electronic transformer (DPET) for feeding critical loads is presented. The PE based transformer is a multi-port converter that can connect to medium voltage levels on the primary side. Bidirectional power flow is provided to the each module. The presented structure consists of three stages: an input stage, an isolation stage, and an output stage. The input current is sinusoidal, and it converts the high AC input voltage to low DC voltages. The isolated DC/DC converters are then connected to the DC links and provide galvanic isolation between the HV and LV sides. Finally, a three-phase inverter generates the AC output with the desired amplitude and frequency. The proposed DPET is extremely modular and can be extended for different voltage and power levels. It performs typical functions and has advantages such as power factor correction, elimination of voltage sag and swell, and reduction of voltage flicker in load side. Also in comparison to conventional transformers, it has lower weight, lower volume and eliminates necessity for toxic dielectric coolants the DPET performance is verified in MATLAB simulation.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6395